The dynamics of speciale fficiency of sportsmen, who specialize in middle distance running - Рода, Ольга Борисівна; Roda, Olha B (Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, 2014)
In sports training man tries to broaden the boundaries of his own capacities and the physical efϐiciency is an informative index, which deϐines a set of properties of the organism and, in the ϐirst place, the efϐiciency of blood ϐlow and breathing mechanisms. In the article the impact of training load on the bodies of athletes, who specialize in middle distance running is analyzed and the dynamics of special efϐiciency, physiological mechanisms, responsible for the quality of athletes’endurance, is determined.The dynamics of female athletes’ special efϐiciency manifestation has cyclical character and depends on the hormonal status change inϐluence on the athletes’ body during the biological cycle. Special efϐiciency of male athletes has tendency of gradual results growth, which is explained by the functional possibilities change, resulted by the effective inϐluence of training loads on their body. The highest efϐiciency has been found in the second and fourth phases, the lowest one - in the third and especially in the ϐirst and ϐifth phases of MC. This is due to the increased functionality of the cardiovascular system and the effectiveness of powerensuring in the second and fourth phases and its decrease in the ϐirst and ϐifth phases of MC, leading to stress of adaptation processes of women’s bodies during these phases. As for men, their dynamics of special efϐiciency tended to gradual increase of the results, that, we think, can be explained by the growth of functional capabilities of the cardiovascular system and the ffectiveness of power-ensuring on account of effective inϐluence of training loads upon their organism.
Keywords: heart rates; menstrual cycle; lactate